2001
DOI: 10.1136/oem.58.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Are neck flexion, neck rotation, and sitting at work risk factors for neck pain? Results of a prospective cohort study

Abstract: Objective-To study the relation between neck pain and work related neck flexion, neck rotation, and sitting. Methods-A prospective cohort study was performed with a follow up of 3 years among 1334 workers from 34 companies. Work related physical load was assessed by analysing objectively measured exposure data (video recordings) of neck flexion, neck rotation, and sitting posture. Neck pain was assessed by a questionnaire. Adjustments were made for various physical factors that were related or not related to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
258
4
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(305 citation statements)
references
References 15 publications
18
258
4
11
Order By: Relevance
“…Sustained cervical postures at work such as forward head posture [6,15] and sustained neck flexion [2,33,35] have been found in previous research to be associated with neck and shoulder pain. For instance, Cagnie et al [6] reported that office workers who hold their neck in a forward bent posture for a prolonged time have 2.6-fold greater odds of developing neck pain.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Sustained cervical postures at work such as forward head posture [6,15] and sustained neck flexion [2,33,35] have been found in previous research to be associated with neck and shoulder pain. For instance, Cagnie et al [6] reported that office workers who hold their neck in a forward bent posture for a prolonged time have 2.6-fold greater odds of developing neck pain.…”
Section: Discussionmentioning
confidence: 68%
“…Reports of 1-year prevalence vary from 15 to 44% [9,10,33]. Prevalence of neck pain is even higher in office workers than in the general community, reaching levels as high as 50 to 60% [2,6,8,19]. Neck pain can impact on the ability to perform normal daily activities, and the resultant treatment costs and work loss contribute to a substantial economic burden for both the individual and society [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Materials: 20 marbles and two bowls with a 14-cm diameter positioned at crown height and at table height. Table 2 Risk factors operationally defined in: nature of the risk factor (summarized), total duration, intensity, or frequency of the exposure, and the axis (i.e., longitudinal, transversal, sagittal) were the movement or posture of the neck or shoulder was performed Nature of risk factor >90 [53][54][55] X, item consistently referred to, but inconsistently operational defined; MVC, Maximal voluntary contraction; <, less than; >, more than; -, no operational value defined in literature; (A) frequency, intensity, and total duration of the exposure; and (B) the plane or axis were the movements or posture is performing…”
Section: Repetitive Overhead Reaching Testmentioning
confidence: 99%
“…Videos of a wide range of manual materials handling (MMH) tasks were selected from the SMASH cohort that has been described before (Ariëns et al, 2001;Hoogendoorn et al, 2000). Briefly, in this cohort, risk factors of musculoskeletal disorders were studied in workers from various industrial and service branches, for example, in the metal, chemical, pharmaceutical, food and wood construction industry; waste processing, insurance and distribution companies.…”
Section: Data Collectionmentioning
confidence: 99%